Senza fissa dimora. Vischiosità parassitarie - Vincenzo Cuomo (Kaiak, 2020)
The essay addresses, first of all, the theme of the structural ambivalence of parasitic relationships, consisting in the passage, always possible, from "predation" to "symbiosis". Secondly, the essay reflects on the paradoxical and "sticky" logic of parasitism, a logic that can only be addressed through para-consistent logical theories. Finally, after talking about parasitic architecture, the text proposes the distinction between the notion of phenotypic symbiosis and that, broader and more encompassing, of hybridization symbiosis.